Persistent frequent attenders in primary care: costs, reasons for attendance, organisation of care and potential for cognitive behavioural therapeutic intervention - Morriss, Richard K.; Kai, Joe; Atha, Christopher; Avery, Anthony; Bayes, Sara; Franklin, Matthew; George, Tracey; James, Marilyn; Malins, Samuel; McDonald, Ruth; Patel, Shireen; Stubley, Michelle; et al. (BioMed Central, 2012)
Background: